Neuroprotective Effect of Danhong Injection on Cerebral Ischemia-Reperfusion Injury in Rats by Activation of the PI3K-Akt Pathway - Chen Feng; Haofang Wan; Yangyang Zhang; Li Yu; Chongyu Shao; Yu He; Haitong Wan; Weifeng Jin (Frontiers Media S.A., 2020)
Many traditional Chinese medicines, including Danhong injection (DHI), can be used to treat cerebral ischemia-reperfusion injury and have neuroprotective effects on the brain; however, few studies have explored the mechanism by which this effect is generated. In this study, we investigated the neuroprotective effect of DHI against cerebral ischemia-reperfusion injury mediated via the PI3K-Akt signaling pathway. After establishing the model of middle cerebral artery occlusion (MCAO), 60 male Sprague-Dawley rats were allocated to six groups as follows: sham, MCAO, DHI (MCAO + DHI), LY294002 (MCAO + LY294002 [PI3K-Akt pathway specific inhibitor]), DHI + LY294002 (MCAO + DHI + LY294002), and NMDP + LY294002 (MCAO + NMDP [nimodipine] + LY294002). Hematoxylin and eosin (HE) and terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) staining were used to evaluate the pathological changes of brain tissue and the degree of neuronal apoptosis. Real-time quantitative polymerase chain reaction (qRT-PCR), western blot analysis and enzyme-linked immunosorbent assays were used to measure the expression of Bad, Bax, Bcl-2, Bim, P53, MDM2, Akt, PI3K, p-Akt, p-PI3K, and Cyt-C. Compared with the MCAO group, brain tissue cell apoptosis was significantly reduced in the DHI group, and the brain function score was significantly improved. In addition, the expression of pro-apoptotic factors (Bad, Bax, and Bim) was significantly downregulated in the DHI group, while expression of the anti-apoptotic factor Bcl-2 was significantly upregulated, and expression of the apoptotic gene p53 was also significantly attenuated. Moreover, this neuroprotective effect was attenuated by the PI3K-Akt signaling pathway inhibitor (LY294002). Thus, our results confirmed the neuroprotective effects of DHI in rats with ischemia-reperfusion injury and indicate that these effects on the brain are partly generated by activation of the PI3K-Akt signaling pathway.